Tetraalkylammonium and phosphonium salt for asphaltene dispersion; experimental studies on interaction mechanisms - Shirin Baghersaei; Babak Mokhtari; Nahid Pourreza; Bahram Soltani Soulgani (Egyptian Journal of Petroleum)
Asphaltenes deposition is one of the most severe problems in the petroleum industry, imposing high costs on oil producer companies. The use of chemical dispersants reduces the risk of asphaltene deposition. For this purpose, a variety of chemicals with different structures and functional groups were designed and synthesized. Organic quaternary salts, such as ionic liquids, have been widely used to control asphaltene deposition over the last two decades, but the mechanism of their interaction with asphaltene has not been studied in detail. In this study, the interaction of ten commercial quaternary ammonium and phosphonium salts with asphaltene molecules was investigated using ultraviolet-visible (UV-Vis) spectroscopy. It was observed that the size, shape, and hydrophobicity of their cations or anions play an essential role in the dispersion of asphaltene aggregations. The results showed that the interaction of these quaternary salts is strongly influenced by the hydrophobic nature of the salt, and salts with more hydrophobic cations and anions, such as tetrabutylammonium iodide, tetrabutylammonium hexafluorophosphate, and cetyltrimethylammonium bromide, can better disperse asphaltene aggregations. The results also revealed that the role of anions such as iodide, and hexafluorophosphate in the dispersion of asphaltene aggregates is more important than cations. In addition, the results showed that except for tetramethylammonium bromide, the efficiency of the salts was increased with increasing concentration.